Trimetazidine attenuates neuroinflammation via TLR4/NF-KB pathway inhibition in lipopolysaccharides-induced dementia in rats - Nadia S. Mahmoud, Marawan A. Elbaset, Ola A.M. Mohawed, Hanaa H. Ahmed (Journal of Applied Pharmaceutical Science, 2024)
Neurodegenerative dementia impairs mental ability and short-term memory. This study investigated the effectiveness of trimetazidine (TMZ) in mitigating lipopolysaccharides-induced dementia in rats. Fifty male rats were randomly assigned into five groups; normal control, dementia, whereas other groups represented as dementia groups administered with 20, 40 mg/kg of TMZ, and 10 mg/kg of memantine, successively. Behavioral testing demonstrated a cognitive decline in dementia rats. Moreover, treatment with TMZ or memantine revealed a substantial decline in serum tau and phosphorylated tau with concurrent amelioration of serum Amyloid beta 1-42, neurogranin, 3-methoxy4-hydroxyphenyl glycol, APL1b25, APL1b27, and APL1b28 levels. Furthermore, such treatments yielded a significant down-expression of hippocampal toll-like receptor 4, NF-kB, cyclooxygenase-2, tumor necrosis factor-α, inducible nitric oxide synthase, caspase-3, and over-expression of Bcl-2 gene along with remarkable improvement in the hippocampal histoarchitecture as well as in the ionized calcium-binding adapter molecule 1 immunostaining compared the derangement in the dementia group. This study sheds light on TMZs neuroprotective effect on dementia pathophysiology by counteracting neuroinflammation. In conclusion, this study underscores the potential of TMZ in attenuating lipopolysaccharide-induced dementia in rats, offering significant cognitive and molecular benefits. The observed improvements in cognitive performance, serum markers, and hippocampal gene expression patterns collectively highlight TMZs neuroprotective capacity, suggesting its viability as a promising therapeutic intervention for addressing neurodegenerative dementia.
Keywords: Dementia, lipopolysaccharides, neuroinflammation, rats, trimetazidine